2019
DOI: 10.1371/journal.pone.0208610
|View full text |Cite
|
Sign up to set email alerts
|

Iron levels, genes involved in iron metabolism and antioxidative processes and lung cancer incidence

Abstract: BackgroundLung cancer is the most common adult malignancy accounting for the largest proportion of cancer related deaths. Iron (Fe) is an essential trace element and is a component of several major metabolic pathways playing an important role in many physiological processes. In this study we evaluated the association between Fe concentration in serum, iron metabolism parameters and genetic variaton in 7 genes involved in iron metabolism and anti-oxidative processes with the incidence of lung cancer in Poland.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…In pregnancy, and especially in severe inflammations, the interpretation of iron concentration results may be difficult [1,27]. Ferritin is considered an indicator of iron storage concentrations, but at the same time is an acute phase protein and its level increases in inflammation [28,29]. Correlations of iron concentrations with hepcidin levels have also been studied in recent years [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancy, and especially in severe inflammations, the interpretation of iron concentration results may be difficult [1,27]. Ferritin is considered an indicator of iron storage concentrations, but at the same time is an acute phase protein and its level increases in inflammation [28,29]. Correlations of iron concentrations with hepcidin levels have also been studied in recent years [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…This has made it a desirable target for cancer treatment and prevention. 19 Previous studies have shown that iron metabolism may contribute to certain cancers, including lung cancer, 20 leukemia, 21 prostate cancer, 22 and kidney cancer. 23 However, the prognostic signature of iron metabolism in GC needs to be adequately explored.…”
Section: Discussionmentioning
confidence: 99%
“…Hodgkin's lymphoma, lung, colorectal, pancreatic and breast cancers are also affected by this increase [49][50][51][52][53][54][55][56][57]. This ferritin increase is a reliable prognostic biomarker for ovary, lung and breast cancers [44,58,59].…”
Section: Iron and Fe-proteins As Cancer Biomarkersmentioning
confidence: 97%